Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„ØªØ¯Ø±ÙŠØ¨ ÙÙŠ Ø±ÙØ¹ Ø£Ø¯Ø§Ø¡ Ø§Ù„Ø¹Ø§Ù…Ù„ÙŠÙ† Ø¨Ø§Ù„Ù…Ø¤Ø³Ø³Ø© Ø§Ù„Ø¯Ø¨Ù„ÙˆÙ…Ø§Ø³ÙŠØ© Ø¨Ø§Ù„Ø¯ÙˆÙ„ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© - Abdul Malik Karim Amrullah; Ahmed Ramdhan Abugren; Maryam Abdullah Kashidan (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2019)
Activities that aim to increase knowledge and experience that affect a person's attitude can be categorized as learning. Islam motivates people to continue learning throughout their lives, including employees. The implementation of Islamic recommendations for learning can be seen in career training in the Islamic State. Career training is a crucial subject in diplomatic institutions such as the Ministry of Foreign Affairs, especially if strategic training is added. Therefore it is essential to review the training strategies of diplomatic institutions and their impact on improving employee performance. This study describes the effects of career training strategies in enhancing employee performance related to achieving the organization's mission, setting goals and decision-making processes, external environment, competition, and complementary components to the general strategy of the organization. The research methodology used is the quantitative descriptive approach. The research subject consisted of 485 employees of the Libyan Ministry of Foreign Affairs with a random sample of 192 employees. Research results: 1. training strategies in the organizational mission component can improve employee performance, 2. training strategies for setting goals and decision-making components can improve employee performance, 3. training strategies affect the external environment, competition, and parts complement each other with general strategies organization